6 Pengaruh Harga Minyak Dunia, Kurs Dolar Dan Bi Rate Terhadap Harga Saham Perusahaan Transportasi Yang Terdaftar Di Bei Periode 2014 - 2018 - Desiana Rachmawati (Jurnal Manajemen Dirgantara, 2019)
This study aims to determine the effect of macroeconomic factors, namely world oil prices, dollar exchange rate and BI Rate partially on share prices of transport companies listed on the Indonesia Stock Exchange (BEI) in the period 2014 to 2018. This research is a quantitative study that uses quantitative time series data for 5 (five) years. The independent variables used in this study are the oil price (X1), the dollar exchange rate (X2) and the BI Rate (X3) with the dependent variable being the stock price (Y). Hypothesis testing uses multiple linear regression test with the help of SPSS 15. The results show there is a significant negative effect on world oil prices and dollar exchange rate on stock prices. World oil prices and dollar excange rate will have an impact on rising company costs, thereby reducing profits. The decline in profits will affect the level of demand that will be reduced to the stock so that the stock price will fall. While BI Rate has a significant positive effect on stock prices because investors in transport companies are foreign investors who are interested in investing when a country's interest rates rise. The demand for shares from foreign investors will increase with the increase in the BI Rate and will cause an increase in share prices